2010
DOI: 10.1021/jp912120n
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Binding of Arachidonic Acid to Mammalian 15-Lipoxygenases

Abstract: Mammalian 15-lipoxygenases (15-LOs) are key pharmaceutical targets under strong investigation because of their implication in atherosclerosis and cancer. Here, we present an atomic-level study of the binding modes of arachidonic acid (AA) to rabbit reticulocyte 15-LO, with a particular insight into the 15-LO:AA complexes consistent with known catalytic activity. We take into account both ligand and protein flexibility, by combining protein-ligand docking techniques and molecular dynamics simulations. We have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 64 publications
7
51
0
Order By: Relevance
“…12 In contrast, such interdomain movement was not observed for s-LOX1. 9 (iii) Alternative molecular conformation: employing proteinligand docking techniques and molecular dynamics simulations, we have reevaluated the original X-ray coordinates for the r-12/15LOX-inhibitor complex, and the results suggested that the enzyme undergoes conformational changes upon ligand binding, 16 as reported by Choi et al…”
mentioning
confidence: 78%
“…12 In contrast, such interdomain movement was not observed for s-LOX1. 9 (iii) Alternative molecular conformation: employing proteinligand docking techniques and molecular dynamics simulations, we have reevaluated the original X-ray coordinates for the r-12/15LOX-inhibitor complex, and the results suggested that the enzyme undergoes conformational changes upon ligand binding, 16 as reported by Choi et al…”
mentioning
confidence: 78%
“…Also, a cationic arginine near the entrance of the cavity has been shown to stabilize the carboxylate head of the fatty acid (13). Computational docking studies based on x-ray crystallography data further support the boot-shaped substrate channel (14,15). For some LOXs, carboxylate head-first binding has been suggested to explain differing specificity or double dioxygenation of AA (16,17).…”
Section: Lipoxygenases (Loxs)mentioning
confidence: 84%
“…First, the same orifice is used in rabbit 15S-LOX according to docking studies (14). For 11R-and 15S-specificity, the same hydrogen must be abstracted in the initial step of catalysis; thus, substrate binding should also be identical.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, arachidonic acid is preferred by the 12-lipoxygenating Ile410Ala mutant (15-H(p)ETE/13H(p)ODE ratio of 79:21). According to MD simulations [120,131] linoleic acid and arachidonic acid share a common overall orientation at the active site. However, arachidonic acid is bound closer to the active site helix α18 and has a limited degree of motional freedom.…”
Section: Monooxygenation Of Free Fatty Acidsmentioning
confidence: 99%
“…However, arachidonic acid is bound closer to the active site helix α18 and has a limited degree of motional freedom. The tail of linoleic acid fluctuates more freely and adopts a number of energetically similar conformations at the active site [120,131].…”
Section: Monooxygenation Of Free Fatty Acidsmentioning
confidence: 99%